Association between resolved hepatitis B virus infection and femoral and spinal bone mineral density in American adults: a cross-sectional study - Yang, Yan; Zeng, Jing; Zhang, Tingting; Wang, Jinjing; Fan, Xiaojing; Wang, Qiaomin; Wang, Xuan; Qi, Zhengrong; Fang, Yi (Frontiers in Endocrinology, 2023)
Abstract Background: Hepatitis B virus (HBV) infection is a global health concern that can potentially affect bone health. However, the specific association between resolved HBV infection and bone mineral density (BMD) remains unclear. This cross-sectional study aimed to investigate the potential association between resolved HBV infection and femoral and spinal BMD in adults in the United States. Methods: This cross-sectional study included participants aged 20-79 years with negative HBV surface antigen (HBsAg) from the 2005-2010, 2013-2014, and 2017-2018 cycles of the National Health and Nutrition Examination Survey. Resolved HBV infection was defined as negative HBsAg with positive HBV core antibody. BMD was measured using dual-energy X-ray absorptiometry. Propensity score matching (PSM) was performed to balance baseline characteristics. Results: A total of 10,333 eligible participants were identified and matched, of whom 737 (7.1%) had resolved HBV infection. Men with resolved HBV infection had significantly lower femoral and spinal BMD compared to those with no HBV infection, both before and after PSM. In the matched population, resolved HBV infection in men was negatively associated with femoral BMD (β= -0.024, 95% CI: -0.047 to -0.002, p = 0.0332) and spinal BMD (β= -0.025, 95% CI: -0.048 to -0.002, p = 0.0339). Postmenopausal women exhibited similar trends to men, while premenopausal women showed a tendency towards higher BMD, although statistical significance was not consistently achieved. Subgroup and sensitivity analyses supported the robustness of the findings. Conclusions: The study suggests a negative association between resolved HBV infection and femoral and spinal BMD in adult men in the United States. It highlights the importance of routine bone density assessments and the consideration of anti-osteoporotic therapy, if necessary, in individuals with resolved HBV infection.